(untitled) (Research, Society and Development, 2021)
This article is the result of a bibliographical research with the objective of presenting a brief history of the practice of Systemic Law in Brazil as a tool in the application of Restorative Justice dynamics, highlighting its importance in the current Brazilian legal context. The study is part of an ongoing master’s research that investigates the performance of 7 (seven) magistrates in Brazil about the practice of Systemic Law. It presents the importance of this practice, considering its creation and adaptation by a Brazilian judge, Dr. Sami Storch, based on Family Constellations, a therapeutic procedure created by Bert Hellinger. Along the theoretical reflection, it is proposed to think about the contrast between Restorative Justice and Retributive Justice, bringing the tools that can be used for the exercise of the former, which are: mediations, peace or restorative circles, participative practices, systemic law with the protagonism of the latter. Supported by the UN Declaration - United Nations Organization - the text shows the regulation of Restorative Justice practices in the world, through three resolutions in the years 1999, 2000 and 2002, whose documents serve as reference for the Restorative Justice work in the signatory countries of the organ. In Brazil, Restorative Justice has its legal mark with the Charter of Brasília, which kept the characteristics contained in the UN Resolution 2002/12. We conclude that the principles of Systemic Law, therefore, constitute the practice of restorative justice, and these two approaches are complementary. We are still far from a generalized implementation, since to approach Systemic Law is to apply the practice of legal science in face of this therapeutic bias, where it is glimpsed to use it to treat issues that generate conflicts, especially during the formation of the bachelor in Law.